Selective weakening of mineralised synthetic particles by high voltage pulses. (15th January 2020) - Huang, Wei; Shi, Fengnian
Highlights: Synthetic particles were cast with and without embedded metalliferous minerals. The metalliferous grain-induced high voltage pulse selective weakening is confirmed. The barren synthetic particles do not exhibit a statistically significant weakening effect. HVP weakening benefits can be maximised by removing the barren rocks from the process. Abstract: The phenomena of high voltage pulse (HVP) selective breakage and HVP weakening have been reported separately in the literature, but the relation between the two HVP applications has previously not been investigated. Synthetic particles made of Epirez high strength grout were cast with and without embedded metalliferous minerals of chalcopyrite and pyrite and used in a study of HVP selective breakage and weakening. When metalliferous grains were embedded in the grout, there were added either as a single grain occurrence or as a fine disseminated texture. The HVP products were assessed using the JKRBT breakage characterisation method for the mineralised particles and the barren particles (with no metalliferous minerals contained), respectively. It has been found that the HVP weakening effect mainly occurs in the mineralised particles, with a reduction in particle competence (indicated by the relative change in A × b value) between 172% and 200% for the pyrite fines dispersed synthetic particles, and 70% relative reduction for the single chalcopyrite grain embedded synthetic particles. The barren synthetic particles do not exhibit a statistically significant weakening effect and appear much more competent than the mineralised particles after HVP treatment. This finding suggests that in mineral processing circuit design utilising the HVP technology, benefits associated with HVP weakening on the downstream comminution process would be maximised by combining the HVP pre-concentration and weakening applications, in doing so removing the barren unweakened rocks from the process.